The Effect of Lateral Opening Wedge Distal Femoral Varus Osteotomy on Tibiofemoral Contact Mechanics Through Knee Flexion. Issue 13 (November 2018) - Wylie, James D.; Scheiderer, Bastian; Obopilwe, Elifho; Baldino, Joshua B.; Pavano, Colin; Macken, Craig J.; Bell, Ryan; Mazzocca, Augustus D.; Arciero, Robert A.; Imhoff, Florian B.
Background: Lateral opening wedge distal femoral osteotomy (DFO) unloads a diseased lateral compartment of the knee in patients with genu valgum. To the best of our knowledge, there are no biomechanical studies investigating the effect of knee flexion on contact pressure and area after DFO. Hypothesis: As knee flexion angles increase, DFO will be less effective at unloading the lateral compartment of the knee. Study Design: Controlled laboratory study. Methods: Lateral opening wedge DFO was performed, correcting a mean of 7°, in 10 cadaveric knees using plate fixation. Tibiofemoral contact pressure was measured in 0°, 15°, 30°, 45°, 60°, and 75° of knee flexion before and after osteotomy using electronic sensors. Peak contact pressure (PCP), mean contact pressure (MCP), and contact area were measured for each condition. Anatomic dissection quantified the tibiofemoral contact position on the distal femur in all degrees of flexion. Mixed-effects regression analyses were used to compare the change in variables before and after osteotomy and between flexion angles. Results: One sample had to be excluded because of tibiofemoral arthritis. MCP decreased in the lateral compartment after DFO throughout all degrees of flexion (all P < .05) but to the greatest extent in 0° of flexion. When examining the percentage of MCP in the lateral compartment, this decreased after DFO at 0° (70.4% to 40.0%; P < .001), 15° (65.1% to 52.1%; P < .001), 30° (60.7% to 52.0%; P = .003), 45° (55.8% to 49.7%; P = .033), and 60° (51.9% to 44.2%; P = .010) but not at 75° (50.2% to 45.3%; P = .112). PCP decreased in the lateral compartment after DFO at 0° (2.41 to 1.34 MPa; P < .001), 15° (2.50 to 1.81 MPa; P < .001), 30° (2.28 to 1.93 MPa; P = .039), 45° (2.21 to 1.73 MPa; P = .005), 60° (2.15 to 1.71 MPa; P = .009), and 75° (1.95 to 1.49 MPa; P = .012). The percentage of contact area decreased in the lateral compartment in full extension (68.7% to 48.1%; P = .007) but not at any other degree of flexion (all P > .05). Conclusion: DFO decreased lateral compartment pressure. However, it had the greatest effect in full knee extension. Clinical Relevance: DFO decreased contact pressure in the lateral compartment but more effectively decreased contact pressure in the more anterior aspects of the femoral articular cartilage.